Is your AoL process overly complex? - Karen A. Tarnoff; Kathleen J. Barnes; Eric D. Bostwick (Organization Management Journal (OMJ), 2023)
Purpose - The purpose of this study is to identify signs of unnecessary assurance of learning (AoL) complexity and to provide suggestions for simplifying the AoL processes. Design/methodology/approach - While this paper is grounded in the existent AoL literature, the paper also presents several anecdotal observations from the authors' practical knowledge in designing, leading, maintaining and consulting on AoL systems and processes. Findings - Based on both a conceptual review of AoL literature and the authors' own experiences, the authors outline 13 specific symptoms of unnecessary AoL complexity, identify potential underlying causes for each symptom and propose practical solutions that can increase the efficiency and effectiveness of dysfunctional AoL systems and processes. Research limitations/implications - Although this work is grounded in the existent AoL literature, the present paper presents several anecdotal observations from the authors' experiences. While the intent is to provide guidance that is actionable, it is understood that variability exists within and across schools and programs. Future research is needed to provide a more formal structure for reviewing AoL complexity, efficiency and effectiveness. Practical implications - While future research is needed to provide a more formal structure for reviewing AoL complexity, efficiency and effectiveness, the intent of this paper is to provide guidance that is actionable with the understanding that variability exists within and across schools and programs. Social implications - Society increasingly is demanding accountability from institutions of higher learning, and properly structured AoL programs can provide evidence of institutional effectiveness in preparing students to be productive members of society in their chosen fields of study. Stated succinctly, "although accountability matters, learning still matters most" (Angelo, 1999, n.p.). Originality/value - Consideration of the 13 symptoms presented here along with other drivers that are unique to each school and program should result in the identification and development of practicable remedies to simplify AoL processes and systems, increase efficiency and effectiveness and improve the documentation of improvements to student learning.
Keywords: 650; Accreditation; AoL complexity; Assessment; Assurance of learning; Simplifying AoL